Cervico-ocula-acusticus syndrome of Wildervanck: case report - Say, Burhan; Balcı, Sevim; Israel, Richard; Yalaz, Kalbiye; Tınaztepe, Behçet; Erbengi, Aykut; Sümer, Nilüfer (The Turkish Journal of Pediatrics, 1973)
A patient with Wildervanck’s syndrome who also had an occipital meningocele is presented. It is suggested that more detailed examination of patients with this syndrome as well as with other forms of spinal dysrhythmism will result in uncovering an increased number of cases with internal lesions. We thank N. Dogruel for his help in the study of this patient. We are also grateful to Misses N. Hatipoglu, G. Güven and G. Lee for their technical assistance.